STUDY ON UTILIZING FLY ASH FOR CASTABLE REFRACTORY - I GUSTI NGURAH ARDHA; MUCHTAR AZIZ (Puslitbang tekMIRA, 2007)
Fly ash could be utilized as alumina and silica sources material. It could be treated by the following processes of demagnetisation, sinterization, grinding, mixing with crushed bricks as well as fired cement to create acid based on castable refractory. Sinterization changes alumina and silica signifi- cantly into mullite. The standard measurement of pyrometric cone equivalent (PCE) is used to under- stand the temperature resistance of the studied castable refractory based fly ash. The temperature resistance seems to increase after contacting with high temperature at longer time or repeatedly until reaching its Si-Al stabilization phase.